Book Reviews. (1st June 2017) - Horlik, Veronika; Souleles, Nicos; Turner, Renée
Sloppy Craft, Postdisciplinarity and the Crafts, Elaine Cheasly Paterson and Susan Surette (eds) (2015) London: Bloomsbury Academic, 200 pp., ISBN: 9781472534880, h/bk, £22.00The Routledge International Handbook of the Arts and Education, Mike Fleming, Liora Bresler and John O'toole (eds) (2015) Abingdon and New York: Routledge, 424 pp., ISBN: 9780415839211, h/bk, £131.00Against Value in the Arts and Education, SAM Ladkin, Robert Mckay and Emile BOJESEN (eds) (2016) London: Rowman & Littlefield International, 446 pp., ISBN: 178348490X, p/bk, £ 26.95